A generalized bag-like boundary condition for fields with arbitrary spin. (July 2015) - Stokes, Adam; Bennett, Robert
Abstract Boundary conditions (BCs) for the Maxwell and Dirac fields at material surfaces are widely-used and physically well-motivated, but do not appear to have been generalized to deal with higher spin fields. As a result there is no clear prescription as to which BCs should be selected in order to obtain physically-relevant results pertaining to confined higher spin fields. This lack of understanding is significant given that boundary-dependent phenomena are ubiquitous across physics, a prominent example being the Casimir effect. Here, we use the two-spinor calculus formalism to present a unified treatment of BCs routinely employed in the treatment of spin- <?CDATA $1/2$?> <?MML 1 / 2 ?><inline-graphic xlink:href="ark:/27927/pgj2j63bv1h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and spin-1 fields. We then use this unification to obtain a BC that can be applied to massless fields of any spin, including the spin-2 graviton, and its supersymmetric partner the spin- <?CDATA $3/2$?> <?MML 3 / 2 ?><inline-graphic xlink:href="ark:/27927/pgj2j63bttp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> gravitino.